Plan for disaster prevention in Los Olivos district - Iglesias León, Silvia (2007)
The paper proposes a Plan of Prevention of Disasters based on a final product: a map – image of vulnerability that was gotten using the digital cartography from a satellite image “IKONOS”. That map – image has permitted the location of vulnerable areas in case of earthquakes taking into consideration the slopes and the building type and use. A study area located at the north of Lima, the District of Los Olivos, was chosen.